The Influence of River Discharge on Nutrient Export and Phytoplankton Biomass Off the Central Chile Coast (33°–37°S): Seasonal Cycle and Interannual Variability - Masotti, Italo; Aparicio-Rizzo, Pilar; Yevenes, Mariela A.; Garreaud, René; Belmar, Lucy; Farías, Laura (Frontiers in Marine Science, 2018)
Using in situ hydro-chemical data and MODIS-SeaWiFS ocean color images as a proxy of river plumes and phytoplankton biomass from 2000 to 2014, this study documents the temporal co-variability of river discharge, plume area, nitrate and phosphate export and phytoplankton biomass in the coastal waters off Central Chile (33º-37ºS). Five major rivers (Maipo, Mataquito, Maule, Itata and Biobío) drain into this region with annual mean discharge ranging from 120 to 1000 m3 s-1. River discharge and coastal plume area present a marked seasonal cycle, reaching maximum values during the winter rainy season (June-September). Export of riverine nutrients also peaks in winter, leading to an increase in phytoplankton biomass within the plumes that can be twice larger than the background values in coastal areas away from the river mouths. Wintertime river discharge, plume area and nutrient export are also correlated at interannual time scales. During a recent extended dry period (2010-2014), river discharges, plume areas and nutrient export clearly decreased by about 50% compared to historical values, reducing significantly the size of the chlorophyll pool within plumes off Central Chile during winter. The potential impacts of droughts are discussed in terms of coastal ecology and primary production, a highly relevant issue considering the projections of a dry climate over Central Chile in the future. Systematic evidence of mega-drought effects upon coastal productivity still does not exist, but it remains a priority to further investigate and quantify these impacts.